Strategi Pengembangan Kreaitivitas Guru dalam Pembelajaran Berbasis IT di Era 4.0 (Studi di SMA Dharmawanita Pare Jawa Timur) - syairozi, Ishak; Basachroh, Jihan Saidah; Damayanti, Dinda Rosa (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Increasing teacher competency in the technological era is a necessity, This effort is the existence of teachers and adaptation to developments that require changes in teaching needs in Era 4.0. Therefore, This research aims to determine strategies for developing teacher creativity in IT Era 40-based teaching at SMA Dharma Wanita Pare, East Java. This research uses a quantitative descriptive method with the data collection method being a questionnaire distributed to respondents and specified sampling. The descriptive method is a method used to describe and interpret existing problems, such as existing conditions and relationships, emerging opinions, ongoing processes, consequences or effects that occur or developing trends. The research subject; 20 teachers who took part in the workshop and 28 student respondents from class XI. Data collection techniques are carried out by filling out questionnaires, observation and interviews, and analysis techniques by reducing data, presenting data and drawing conclusions. The results of this research show strategic steps for habituation in increasing teacher competence, such as teaching approaches with IT applications, using the integrated application mode Canva and ChatGPT, and carry out interesting, fun, and critical teaching techniques that are internalized in IT applications. This encourages curiosity, sharpens imagination and develops students' creativity